Peer‐to‐peer connections: Perceptions of a social support app designed for young adults with cancer. Issue 1 (16th September 2019) - Lazard, Allison J.; Saffer, Adam J.; Horrell, Lindsey; Benedict, Catherine; Love, Brad
Abstract: Objective: Social support is a critical, yet frequently unmet, need among young adults (YAs) with cancer. YAs desire age‐appropriate resources to connect with peers. Peer‐to‐peer mobile apps are promising interventions to provide social support. Peer‐to‐peer apps will be more effective if development incorporates users' input for whether app designs (look and function) afford meaningful connections. Methods: We interviewed 22 YAs to assess perceptions of a peer‐to‐peer app at a YA cancer convention in April 2017. Results: Participants were an average age of 29, mostly female (77%), white (73%), and well educated (68% with 4‐year college degree or higher). Most participants expressed interested in using an app to connect with YAs, but preferences varied by prevalence or rarity of one's cancer diagnosis. YAs shared trade‐offs for profile anonymity versus profiles with more personal information, requests for filter options to connect for varying support needs, and desires for tailored messaging and chat room features (eg, topic‐specific and search capabilities). Conclusion: Findings demonstrate the promise of apps to fulfill YA cancer survivors' unmet peer support needs and provide guidance for app optimization. Clinical implications: Peer‐to‐peer support apps should be designed so users can control their identity and customize features for meaningful connections.